Characterization of synthetic fibers and cotton composites used in prosthetic socket. Issue 1 (March 2021) - Widayat, W; Al-Janan, D H; Wakhidah, D F; Prabowo, D
Abstract: This study aims to determine the bending and impact strength of the laminate composite Co/G/Co (cotton - glass fiber - cotton) and C/G/C (carbon fiber - glass fiber - carbon fiber) that are used by Garuda Medica, an orthotic and prosthetic manufacturer in Tridadi, Sleman Regency, to make prosthetic sockets. Co/G/Co and C/G/C laminate composites with layer variants of 2/1/2 and 4/2/4 for each composite were made by hand layup method. All variants were tested for their flexural and impact strength. The addition of the laminate layer and the replacement of the outer laminate increase the strength of the composite. The replacement of the outer laminate from cotton to carbon increased the strength. The lowest impact strength of the composites, namely the [Co2 /G/Co2 ] variant, has met the requirement of the socket impact strength that is suitable for use. However, the stacking sequence of Co/G/Co and C/G/C are not recommended when viewed from the strength and classification of the constituent laminates.